Oral Insulin Delivery in Diabetic Rats by PLGA Nanoparticles Combined with a Protease Inhibitor (N-Ethylmaleimide) - Ahmed M Faheem; Dalia Abdeĺkader; Mohamed A. Osman; Paul A. McCarron; Sanaa A. El-Gizawy (British Journal of Pharmacy, 2019)
Nanoparticles have shown a certain potential to overcome the drawbacks of oral peptide delivery in the gastrointestinal tract such as low peptide stability and permeability. Insulin PLGA NP were prepared using a modified double emulsion solvent evaporation technique. Insulin PLGA NP were composed from human insulin (5 mg) encapsulated in PLGA 2.5% (w/v) mixed with PEG (2kDa, 5% w/w) and the external aqueous phase contained 1.25% of PVA. The resulting nanoparticles of 202.6 nm diameter and loaded with 33.86 μg insulin per mg of polymer were utilised in this study to examine the hypoglycaemic effect after combination with a protease inhibitor, N-Ethylmaleimide.